2015
DOI: 10.1063/1.4917505
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the complex permittivity and permeability of magnetic nanoparticles

Abstract: The complex permittivity and permeability of superparamagnetic iron-oxide nanoparticles has been quantified using a circular waveguide assembly with a static magnetic field to align the nanoparticle's magnetization. The high sensitivity of the measurement provides the precise resonant feature of nanoparticles. The complex permeability in the vicinity of ferromagnetic resonance (FMR) is in agreement with the nanoparticle's measured magnetization via conventional magnetometry. A rigorous and self-consistent meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Here, the long-range magnetic stray fields and demagnetization effect depend critically on the surfaces and alter the internal magnetic field. The internal magnetic field rules the microwave response and spin-wave (magnon) modes [13] which are of relevance in very different fields ranging from biomedicine [14] to microwave devices [15] and magnonics [16]. Non-flat or irregular surfaces do not allow one to precisely determine the demagnetization factors necessary for a detailed data analysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the long-range magnetic stray fields and demagnetization effect depend critically on the surfaces and alter the internal magnetic field. The internal magnetic field rules the microwave response and spin-wave (magnon) modes [13] which are of relevance in very different fields ranging from biomedicine [14] to microwave devices [15] and magnonics [16]. Non-flat or irregular surfaces do not allow one to precisely determine the demagnetization factors necessary for a detailed data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Often, randomly oriented magnetic NPs have been addressed. [14,15,18] In the research field of magnonics, however, strictly periodic magnetic nanostructures that form artificial crystals are of crucial interest. [16] To fully exploit the rich advantages offered by magnonics technology, it was very recently argued that mastering spin waves with sub-100 nm wavelengths is key [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CMP effect has recently been observed by setting miligrams of magnetic nano-particles inside a special circular waveguide cavity 11 , where the CMP coupling can be analyzed in the simple 1D configuration by using either the straightforward transfer matrix method 11 , or equivalently, the 1D scattering theory 12 . It is found that the CMP coupling enables quantifying the complex permeability of magnetic nanoparticles with high sensitivity, which was an outstanding challenge for the biomedical applications of magnetic nanoparticles 11 . In 3D microwave cavities, it is shown that the CMP coupling leads to the electromagnetically induced transparency (EIT), which is tuneable by applying an external magnetic field 5 .…”
mentioning
confidence: 99%
“…Recently, strong coupling between a microwave cavity mode and ferromagnetic resonance (FMR) has been realized at room temperature [6][7][8][9][10][11][12][13][14][15][16][17] . Exchange interactions lock the high density of spins in YIG into a macro-spin state, leading to strong coupling with a cavity mode which can be adjusted using an external magnetic field.…”
mentioning
confidence: 99%